Redneck (2017), volume 3 ebook Longhorns. - Cates, Donny (Redneck (2017), 2019)
With life at its absolute lowest for the Bowman family, they're forced to turn to a clan Bartlett had hoped to avoid for the rest of his very long life. Why? Because it's led by his ex, July Collects REDNECK #13-18. Author: Donny Cates. Illustrator: Lisandro Estherren, Dee Cunniffe . 2019 Skybound, LLC.